Reference ranges for complete blood count in children and adolescents with Down syndrome - Lattuada, Martina; Capitoli, Giulia; Casati, Marco; Lazzerotti, Alessandra; Maglia, Oscar; Ferrari, Giulia Maria; Fossati, Chiara; Biondi, Andrea; Cattoni, Alessandro; Corti, Paola (Frontiers in Pediatrics, 2024)
Down syndrome (DS) is linked to unique hematopoietic characteristics that affect complete blood count (CBC) parameters. Accurate reference ranges are essential for proper CBC interpretation in this population. This retrospective study analyzed 2627 CBCs from 481 DS patients, aged 31 days to 18 years, at a tertiary care center in Italy. Patients with significant comorbidities were excluded to ensure a homogeneous group. CBC parameters were assessed to establish age-and sex-specific reference ranges. Centile charts were developed for each parameter, and an online tool was created to allow clinicians to compare individual CBC results with the new ranges. Comparisons with the general pediatric population revealed significant differences, particularly in hemoglobin, hematocrit, and mean corpuscular volume, which were higher in DS (p<0.001). In contrast, a significant percentage of CBCs showed white blood cell counts below the 2.5th centile of healthy controls (p<0.001), except for the 31 days-1 year age group. A similar trend was observed for lymphocytes (p<0.001) in the 1-18 years group. These newly established DS-specific reference ranges provide clinicians with a crucial tool for evaluating CBC results, potentially reducing unnecessary tests and emphasizing the need for tailored clinical assessment in managing this unique population.